2013
DOI: 10.1155/2013/820695
|View full text |Cite
|
Sign up to set email alerts
|

The Cardioprotective Effects of Citric Acid and L-Malic Acid on Myocardial Ischemia/Reperfusion Injury

Abstract: Organic acids in Chinese herbs, the long-neglected components, have been reported to possess antioxidant, anti-inflammatory, and antiplatelet aggregation activities; thus they may have potentially protective effect on ischemic heart disease. Therefore, this study aims to investigate the protective effects of two organic acids, that is, citric acid and L-malic acid, which are the main components of Fructus Choerospondiatis, on myocardial ischemia/reperfusion injury and the underlying mechanisms. In in vivo rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 32 publications
2
73
0
Order By: Relevance
“…It has been suggested that cranberry (Vaccinium macrocarpon) fruit powders, containing organic acids, as well as polyphenolic compounds including phenolic acids and displaying inhibition of both α-glucosidase and α-amylase, could be developed for the management of postprandial hyperglycemia (Pinto et al 2010). In a study of organic acids in Chinese herbs, it was found that organic acids such as citric acid and L-malic acid may be the active ingredients responsible for the cardioprotective effects Fructus choerospondiatis (Tang et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that cranberry (Vaccinium macrocarpon) fruit powders, containing organic acids, as well as polyphenolic compounds including phenolic acids and displaying inhibition of both α-glucosidase and α-amylase, could be developed for the management of postprandial hyperglycemia (Pinto et al 2010). In a study of organic acids in Chinese herbs, it was found that organic acids such as citric acid and L-malic acid may be the active ingredients responsible for the cardioprotective effects Fructus choerospondiatis (Tang et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Diltiazem, a selective L-type Ca 2+ -channel blocker, has been reported to be effective in treating myocardial infarction diseases (15). Clopidogrel, a thienopyridine derivative, and a selective and irreversible antagonist of ADP (P2Y 12 ) receptor, is a commonly used drug in the treatment of ischemic heart disease (20 -22).…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of infarct size using N-BT staining was identical to the method described previously (15). The rats were then sacrificed at the end of 2-h reperfusion.…”
Section: Measurement Of Myocardial Infarct Sizementioning
confidence: 99%
“…The MA supplementation could be a promising treatment for the calcium oxalate stone disease due to its capacity to increase urinary citrate excretion and urinary pH [8]. MA has protective effects on myocardial ischemia/reperfusion injury due to its anti-inflammatory, anti-platelet aggregation, and direct cardiomyocyte protective effects [9].…”
Section: Introductionmentioning
confidence: 99%